Bullying Phenomenon and The Perspective of Islamic Sharia in Society: Literature Review of The Last Ten Years from Various Countries with the Assisted of NVivo - Deris Arista Saputra (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
This research aimed to examine various studies that raised the theme of bullying in numerous countries over the last ten years, and explains how Islamic law provides its perception in preventing and avoiding bullying in social life. The research method applies literature review by reviewing various studies in journal articles. Article searches were carried out using the search engine on the Scopus website with the keyword "bullying phenomenon". The results show that bullying can occur in various locations, starting from educational establishments, workplaces, and even in everyday life. Based on the grouping of bullying locations in schools, it was found that the junior secondary education level was the focus of most research. The study results on the factors that cause someone to experience or become a perpetrator of bullying include family conflict, school playground, school economic index, digital media, and cultural diversity. The impacts of bullying include Exit from the organization, gender stereotypes, characteristics, and academic achievement. The final part is the solution or prevention of bullying, including victims' services, psychosocial well-being, sports participation, family environment, and awareness of the bullying phenomenon. Reflections is becoming increasingly important, and Islam is its source.